Integration of the European market for e-finance: evidence from online brokerage - Martin Schüler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
The internet revolution is said to foster integration of the market for financial services, since consumers are able to shop around at all companies worldwide and firms can easily offer their services on the internet at a minimum of distribution cost. However, the European market for online brokerage displays a different picture. Prices paid for online brokerage differ substantially across European countries. Furthermore, almost no direct cross-border activities take place, i.e. online purchases of stocks are almost always done using a domestic direct broker. It turns out that one of the most important obstacles to integration seems to be the preferences of the consumers for domestic providers. The analyses is partially based on a survey among leading European online brokers.
Keywords: G15; G24; 330; E-Finance; Financial Market Integration; European Union; Electronic Banking; Wertpapierhandel; E-Business; Internationaler Finanzmarkt; Marktintegration; EU-Staaten